On Fixed Point of Difference Polynomials with Meromorphic Function of Finite Order - Gatti, N. B.; Jayarama, H. R.; Naveenkumar, S. H.; Chaithra, C. N. (Communications in Mathematics and Applications, 2023)
In this paper, we investigate \(f(z)\) to be a transcendental meromorphic function of finite order \(σ(f)\) and \(c\in\mathbb{C}\) be complex constants. The authors establish an fixed points about the difference polynomials \(Φ(z)=Δ f(z)-a(f(z))^{n}\), where \(Δ f(z)=f(z+c)-f(z)\). These results extend the related results obtained by Wu and Wu (Fixed points of differences of meromorphic functions, Advances in Difference Equations 2019 (2019), Article number: 453).